Youths quality of life in Nigerian state: link with resilience, locus of control and perceived social supports? (2022)
Cross sectional research design was adopted to examine the relationship between three independent factors (resilience, internal locus of control, perceived social supports) and quality of life. A sample size of four hundred (400) youths between ages 18-30 years (Male=240; Female=160) were selected using a combination of simple random sampling and purposive technique from a population of out-of school youths in Anambra State, Nigeria. Four standardized scales were used for data collection. Pearson Product Moment Correlation (PPMC) and Multiple Regression were used for data analysis. Findings revealed that resilience (r= 0. 146**p<.05), internal locus of control (r= 0.165** p<.05) and social support (r= 0. 658** p<.05) positively correlated with quality of life respectively. There was significant joint contribution of the independent variables to the prediction of quality of life among the respondents F (5,395) = 102.299, P<0.001). The independent variables (resilience, internal locus of control and perceived social supports) when combined accounted for 50.2% (Adj.R2= .502) of the variance in quality of life among out-of school youths in Anambra State. Resilience was the most potent predictor of quality of life among the variables considered in this study (β =.591, t =10.153, P<0.001). Counselling psychologists should institute resilience-focused therapy to build the practical skills of youths to become capable of handling their everyday challenges in order to have an improved quality of life.